PENGARUH IKLAN, KEPERCAYAAN MEREK TERHADAP NIAT BELI MELALUI SIKAP SEBAGAI VARIABEL INTERVENING - JUNIKE MARANATHA NAIBAHO, NOVA (Jurnal Ilmu Manajemen (JIM), 2016)
Communication technology development grows faster. Human’s high demand of communication in making phone’s development keeps on rising and undergoing movement into smartphone. That phenomenon gives phone producers opportunities to create smartphone products with competitive advantages with other brand. Nokia X2 Android Smartphone is the first smartphone released by Microsoft ever since the company had been acquisitioned by Microsoft. This research’s purpose is analyzing and discussing the effect of advertising appeals and brand trust towards purchase intention with attitude as intervening variable. The applied sampling technique was non-probability sampling and judgmental sampling on samples as many as 110 individuals. The population is 19 years old up to 50 years old consumers and had ever saw Nokia X2 advertisement on YouTube. The applied measurement scale in this research likert scale. The researcher used questionnaire as measuring instrument whileas path analysis was used as analysis instrument along with AMOS program. The results of the research showsthat advertising appeals of Smartphone Android Nokia X2 and brand trustis effectpositiveof purchase intention, andthe positive effect also ofattitude. Finally in this study attitude evidence effect of purchase intention. Keywords: advertising appeals, brand trust, attitude, purchase intention